The Rock Island Line - Marvel, Bill (Book collections on Project MUSE., 2013)
This richly illustrated volume tells the story of a legendary railroad whose tracks spanned the Midwest, serving farms and small-town America for more than 140 years. One of the earliest railroads to build westward from Chicago, it was the first to span the Mississippi, advancing the frontier, bringing settlers into the West, and hauling their crops to market. Rock Island's celebrated Rocket passenger trains also set a standard for speed and service, with suburban runs as familiar to Windy City commuters as the Loop.